Influence of particle size and pyrolysis conditions on yield, density and some textural parameters of chars prepared from holm-oak wood - Valenzuela-Calahorro, C; Bernalte-Garcia, A; Gómez-Serrano, V; Bernalte-García, Ma.J. (Journal of Analytical and Applied Pyrolysis, 1987)
Chars were prepared from holm-oak wood (Quercus ilex) using sawdust, cubes (20 × 20 × 20 mm) and octagonal prisms (20 × 20 × 80 mm) by heating in nitrogen under dynamic (sawdust and cubes) and isothermal (sawdust and prisms) conditions to different final temperatures. The yield of char production depends on the wood particle size, heating rate and final temperature. The density of the chars as measured by helium displacement, ϱHe (g/cm3), is influenced by the wood particle size and heating conditions. Chars prepared from holm-oak wood are essentially microporous solids. The apparent surface area and the micropore volume increase only slightly up to the treatment temperature of 500°C, increase greatly up to 800°C and decrease at higher temperatures.
Keywords: biomass; chars; holm-oak; pyrolysis; wood.